Comparativo entre os frameworks de desenvolvimento Web Vaadin e GWT utilizando a biblioteca SmartGWT - Seffrin, Rodolfo (2013)
With the growth of the Internet in recent years, web applications and increasingly robust, the need arise the use of frameworks that help in developing web applications RIA (Rich Internet Application). This study conducted a comparative analysis between two frameworks RIA Web Development: Vaadin and GWT (Google Web Toolkit). With was used SmartGWT component library for assistance in building the graphical interface. Vaadin uses GWT as far as the main element for application development language Java, and closely resemble the style of desktop development. To demonstrate the operation of both an application was developed for monitoring the growth of a child, where the cycle begins at birth, when ending its initial growth phase is complete. The evaluation results indicated that the Vaadin Framework is the most appropriate for use, due to its programming architecture components to be productive and have enjoyable for the end user.